Muhammad Abduh's Thoughts on Building Critical Awareness and Moral Literacy in Prospective History Teachers in The Digital Era - Mardiani, Fitri; Alfairus, Willy; Nadilla, Dewicca Fatma; Prawitasari, Melisa; N.P., Herry Porda (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The accelerated flow of information in the digital era has presented serious challenges for prospective history teacher students, namely the low ability to verify sources and weak awareness of information ethics. This study aims to analyze the thoughts of Muhammad Abduh as a conceptual foundation in building critical awareness and moral literacy for prospective history teacher students in the digital era. The approach used is qualitative through a literature study that focuses on 20 primary references sourced from books, websites, relevant journals accessed using the Google search engine, Google Scholar, Open Access Library, and others. The results of the study show that Abduh's thinking emphasises rationality, ijtihad, And reform can be operationalized into two main competencies: (1) critical awareness in interpreting historical sources reflectively in digital space, and (2) moral literacy in the use of digital media that is ethical, honest, and respects historical truth. Thus, the idea of ​​Muhammad Abduh can be used as a foundation for building a new paradigm for prospective history teachers who are oriented towards critical, moral, and adaptive thinking to the challenges of the digital era.